FIND THE ANSWERS

If f(x) = x2 – 2x and g(x) = 6x + 4, for which value of x does (f + g)(x) = 0?

Answer this question

  • If f(x) = x2 – 2x and g(x) = 6x + 4, for which value of x does (f + g)(x) = 0?


Answers

Answer #1 | 23/07 2015 21:48
(f+g)(x)=f(x)+g(x) (f+g)(x)=x^2-2x+6x+4 (f+g)(x)=x^2+4x+4 (f+g)(x)=0 when: x^2+4x+4=0 factor.. (x+2)(x+2)=0 (x+2)^2=0 So the only value of x that will make (f+g)(x)=0 is x=-2 check... (f+g)(-2)=x^2+4x+4=4-8+4=0
Positive: 66.666666666667 %
Answer #2 | 23/07 2015 14:13
f(x) = x^2 – 2x and g(x) = 6x + 4 (f + g)(x) = x^2 - 2x + 6x + 4 (f + g)(x) = x^2 + 4x + 4 (f + g)(x) = (x + 2)^2 = 0 x = -2
Positive: 66.666666666667 %
Anonymous241301 | 29/11 2020 17:17
algebra trigonometry someone that can do my math homework research proposal
Positive: 66.666666666667 %
Answer #4 | 23/07 2015 21:13
b
Positive: 60 %
Answer #5 | 23/07 2015 14:48
(f+g)(x)=f(x)+g(x) (f+g)(x)=x^2-2x+6x+4 (f+g)(x)=x^2+4x+4 (f+g)(x)=0 when: x^2+4x+4=0 factor.. (x+2)(x+2)=0 (x+2)^2=0 So the only value of x that will make (f+g)(x)=0 is x=-2 check... (f+g)(-2)=x^2+4x+4=4-8+4=0
Positive: 50 %
Answer #6 | 23/07 2015 21:13
f(x) = x^2 – 2x and g(x) = 6x + 4 (f + g)(x) = x^2 - 2x + 6x + 4 (f + g)(x) = x^2 + 4x + 4 (f + g)(x) = (x + 2)^2 = 0 x = -2
Positive: 50 %
Answer #7 | 23/07 2015 14:07
a.–4 b.–2 c.2 d.4
Positive: 50 %
Answer #8 | 23/07 2015 21:07
a.–4 b.–2 c.2 d.4
Positive: 50 %
Answer #9 | 23/07 2015 14:13
b
Positive: 50 %
Anonymous644320 | 30/11 2020 01:07
university assignments for sale doctoral dissertations in nursing can you help me with homework
Positive: 50 %
Anonymous236357 | 01/12 2020 14:57
college essay practice affordable custom essays with reviews essay cheating
Positive: 50 %
Anonymous185725 | 30/11 2020 21:45
essay brainstorming case study article mit college essay
Positive: 50 %
Anonymous607043 | 02/12 2020 07:04
essay assignment middle school ideas for writing a persuasive essay write an opinion essay
Positive: 50 %

Possible answer